Promoting social-emotional competence and wellbeing in university students: a mixed methods exploratory study of a relaxation-based intervention - Dias Rodrigues, Andreia; Marmeleira, José; Pomar, Clarinda; Lamy, Elsa; Veiga, Guida (Frontiers in Developmental Psychology, 2026)
IntroductionThe higher education years represent a critical period for social and emotional development, often marked by elevated stress and challenges to self-regulation that impact students' wellbeing and interpersonal functioning. These demands are particularly relevant for future childhood educators, whose professional effectiveness depends partly on their ability to model and support children's emotional development.MethodsThis mixed-methods, non-randomized study examined the effects of an 8 week psychomotor relaxation program on a small single-group sample of 20 first-year female university students in Education Sciences. Following a 4 week within-subject control phase, participants engaged in biweekly psychomotor relaxation sessions combining body awareness, muscle tone regulation, and breathing exercises. A single-arm repeated-measures design assessed changes in objective and subjective stress indicators, interoceptive awareness, affective states, and psychological wellbeing. Additionally, students' perceptions of the program's personal and professional impact were explored through open-ended questions and thematic analysis.ResultsQuantitative findings revealed selective improvements in emotional and bodily awareness, a reduction in confusion, and an enhanced sense of purpose in life. Qualitative data supported these results, with most students reporting regular use of learned strategies in daily life and recognizing the relevance of these skills for managing classroom stress and fostering children's emotional wellbeing in their future roles as childhood educators.DiscussionThese results reinforce the potential value of integrating body-oriented interventions, particularly those based on relaxation, into higher education curricula to support social and emotional development during this formative life stage.